SHM_3266291_3D Vendel Fragment: Helmet Fragment Depicting Bird Figure - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
3D photogrammetric model of an iron helmet fragment with pressed plate decoration of a bird figure and textile remnants preserved by corrosion. Excavated from Vendel Boat Grave XI in Vendel, Uppsala, it dates from the eponymous Vendel period and is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collections platform

https://dyncoll.ht.lu.se/artifact_view.php?item=978

Link to Sök I Samlingarna

https://samlingar.shm.se/object/9c20477a-4d41-4080-b1fa-cf9eaa171ef1
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; 3D Model; Photogrammetry; Museum Object; Dynamic Collections; Vendel; Vendel Period; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi